Skeletal Muscle Na+ Channel Disorders - Dina eSimkin; Saïd eBendahhou (Frontiers Media S.A., 2011)
Five inherited human disorders affecting skeletal muscle contraction have been traced to mutations in the gene encoding the voltage-gated sodium channel Nav1.4. The main symptoms of these disorders are myotonia or periodic paralysis caused by changes in skeletal muscle fiber excitability. Symptoms of these disorders vary from mild or latent disease to incapacitating or even death in severe cases. As new human sodium channel mutations corresponding to disease states become discovered, the importance of understanding the role of the sodium channel in skeletal muscle function and disease state grows.